Simplification of Workflow-oriented Security Assessment - Yunizal, Edri; Wardana, Aulia Arif; Niarman, Abdurrahman (School of Applied Science, Telkom University, 2023)
One of the protection mechanisms for organizations to protect their data is through information security risk assessment. The main obstacle in this area is asset dependency. Previous research developments tended to produce models that were difficult to implement because they were only applied to small assets, in contrast to the complexity of implementation in the field. This form of problem solving is a workflow-oriented security assessment solution that provides security rationale from a holistic perspective. The weakness of complexity in workflow oriented then became the basis of this research. The proposed solution is a simplification by using combined nodes that enable a modular concept. The modular concept is then applied to a reliable model, a data flow diagram. The study output shows the contribution of offerings with assessment solutions that consider dependencies by simplifying asset complexity in workflows in a modular manner with data flow diagrams.